PLANTAR FASCIITIS: A REVIEW OF 2024 - Kongtong, Worapong; Nemee, Prattana (Journal of Sports Science and Health, 2025)
Plantar fasciitis (PF) is the inflammation of the plantar fascia caused by repetitive excessive stress, which leads to microtrauma and pain at the heel. The pain is most noticeable with the first step after waking up in the morning or after prolonged periods of rest. However, the pain typically subsides after walking a few steps and may eventually disappear. Nonetheless, the pain can return if the foot is subjected to prolonged weight-bearing activities. Diagnosis of PF is performed by a physician or physical therapist using diagnostic ultrasound during a physical examination. PF has a high incidence among various groups and regions, with particularly high prevalence in individuals involved in activities that require prolonged weight-bearing. Risk factors for PF are categorized into intrinsic factors, such as a high body mass index and flat feet, and extrinsic factors, such as prolonged standing, walking, or running, and wearing improper footwear for the activity. In terms of treatment, conservative methods are commonly used and include physical therapy modalities, massage, orthotic devices and medications (either oral or injectable) to relieve pain and promote the healing of the plantar fascia. However, if conservative treatments fail, operative treatments may be considered. Therapeutic exercise is an effective and widely accepted treatment approach for PF. This includes two main types of exercises: stretching exercises targeting the plantar fascia, Achilles tendon, the calf muscles to reduce tightness, and strengthening exercises. These strengthening exercises are divided into two groups: one for elderly or sedentary individuals, and another for young adults and athletes. While the exercise protocols differ, they all aim to strengthen the intrinsic foot muscles and structures associated with the function of the plantar fascia.